Anthropic effect generated by waste in the District of Caleta de Carquín - Huaura - Cruz Nieto, Dante (2019)
The research was carried out in the Caleta de Carquín District, with the objective of characterizing solid waste and obtaining the diagnosis to improve recycling. In addition to knowing the areas of contamination and infectious foci. For this, per capita production, physical composition, solid density and humidity, population habits and opinions regarding management were evaluated. The sample was calculated using the formula of Kunitoshi Sakurai, obtaining 47 homes and the data were operated with basic statistics. The results determined the highest production per capita is in the Town Center of Caleta de Carquín with 0,506 kg / person per day, produces organic waste with 41,34 %, the moisture density is on Friday with 17,11 %, in opinions 85,8 % know about recycling, 61,75 % are not satisfied with the service, in attitudes 80 % place it in a visible place for pick-up, throw it anywhere 9 %, in opinions of the municipal service it should improve with 45,5 % and improve its 27,5 % pick up plan. It is worth mentioning that thewaste caused damage to the countryside and city; So you should make effcient programs